2016
DOI: 10.5513/jcea01/17.4.1820
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and comparison of the content of total polyphenols and antioxidant activity of selected species of the genus Allium

Abstract: The species of the genus Allium are very important crops for human health. They contain many health beneficial substances, such as polyphenols (especially flavonoids), sulphur compounds, vitamins, mineral substances and substances with antioxidant activity. This work has focused on the comparison of total phenolic content and antioxidant activity of selected species of the genus Allium -garlic (Allium sativum L.), chives (Allium schoenoprasum L.), ramson (Allium ursinum L.) and red, yellow and white onion (All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 33 publications
(37 reference statements)
1
11
1
3
Order By: Relevance
“…However, our data were in accordance with Behbahani et al (2017) -24 mg GAE/g dw, but our total flavonoids were lower than 20 mg QE/g dw. In addition, our values for total phenols were higher in ramson and chives than reported values by Lenková et al (2016).…”
Section: Antioxidant Activitycontrasting
confidence: 90%
“…However, our data were in accordance with Behbahani et al (2017) -24 mg GAE/g dw, but our total flavonoids were lower than 20 mg QE/g dw. In addition, our values for total phenols were higher in ramson and chives than reported values by Lenková et al (2016).…”
Section: Antioxidant Activitycontrasting
confidence: 90%
“…Results of current investigation are comparable with findings reported by Shunmugapriya, and Kalaiselvan, (). Dalaram () reported the TPC of fresh garlic as 50.67 ± 1.77 mg/100 g. However, Lenkova, Bystricka, Toth, and Hrstkova () reported TPC of fresh garlic as 105.1 ± 1.81 mg of GAE per 100 g. Kallel et al () found that garlic extracts with methanol in 50/50 ratio contained the highest TPC, followed by ethanol and water extract which strengthen the results of present study. Several factors such as environmental influences on the produce (type of soil, rainfall, and exposure to sun), agronomic conditions (hydroponic culture, biological culture, culture in greenhouses or fields, etc.…”
Section: Resultssupporting
confidence: 74%
“…Lenkova et al. (2016) reported that white and red‐skinned onion possessed 444.3 and 1,313 mgGAE/g total phenols, and 12.29% and 40.58% antioxidant activity values, respectively. Ren, Perussello, Zhang, Gaffney, et al (2018) found that the total phenol contents, antioxidant activity values, and the total flavonoid contents of onion slices dried via hot air varied between 5.50 and 7.76 mgGAE/g, 2.84 and 4.43 mg TE/g, and 2.70 and 4.34 mgQE/g, respectively.…”
Section: Resultsmentioning
confidence: 99%